2021
DOI: 10.1021/acsami.1c06460
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Functionalized Separators for Lithium-Ion Batteries with Ionic Conduction Path Modifications via the γ-Ray Co-irradiation Grafting Process

Abstract: Separators play a vital role in electronic insulation and ionic conduction in lithium-ion batteries. The common improvement strategy of polyolefin separators is mostly based on modifications with a coating layer, which is simple and effective to some extent. However, the improvement is often accompanied by negative effects such as the increase of the thickness and the blockage of the porous structure, resulting in the decrease of energy density and power density. The porous structure of the separators serves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The higher amount of loading can affect the porosity of the coated layer and electrolyte uptake which can lead to heightened resistance at the interface between the cathode and separator, potentially deteriorating the battery performance. 40 The performance of the MC separator prepared with a higher amount of c-MoS 2 (5 mg and 10 mg) has been studied in comparison to 2 mg dispersion. A tape adhesion test revealed that the c-MoS 2 was undetachable from the PP separator; in contrast, the commercial MoS 2 and ce-MoS 2 readily became stuck on the gummed side of the tape, confirming its poor adhesivity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The higher amount of loading can affect the porosity of the coated layer and electrolyte uptake which can lead to heightened resistance at the interface between the cathode and separator, potentially deteriorating the battery performance. 40 The performance of the MC separator prepared with a higher amount of c-MoS 2 (5 mg and 10 mg) has been studied in comparison to 2 mg dispersion. A tape adhesion test revealed that the c-MoS 2 was undetachable from the PP separator; in contrast, the commercial MoS 2 and ce-MoS 2 readily became stuck on the gummed side of the tape, confirming its poor adhesivity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since there are only Li + participating in the electrochemical reactions during the energy conversion process, the Li + transference number (t Li + ), which reflects the contribution of lithium ions to the overall ionic conduction, was calculated using eq 1 by the combination of chronoamperometry and AC impedance analysis. 31 The calculated t Li + of PP and ITE PET separators is 0.53 and 0.59, respectively, as displayed in Figure 4c,d. The higher t Li + value of the ITE PET separator also reveals that the vertical channels possess a relatively higher Li + ion conducting ability than that of the PP separator.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Lee et al [243] developed a polydopamine interlayer between two PE films as a selective layer, thus suppressing the diffusion of the decomposed production of electrolytes. According to this idea, Zhao group [244] fabricated grafted boronated monomer onto the surface of PE to enhance the Li + transference number (t Li + ). The boronated molecule on [241] Copyright 2020, Elsevier.…”
Section: Separatormentioning
confidence: 99%